ANALISIS PENGENDALIAN KUALITAS KAIN RAYON MENGGUNAKAN SIX SIGMA DAN FMEA - Muhammad Krisna Agung; Ari Zaqi Al Faritsy (CV. ALIM'SPUBLISHING, 2024)
XYZ is a company operating in the textile industry and producing rayon fabric. In the production process, defects were still found in the period October 2023 – March 2024. Rayon fabric production was 286973m, consisting of defects in final weft 11643m, wavy 8391m, unwoven 7569m, double weft 6173m, stretch weft 8126m. Based on the problem, it can be solved using the six sigma method and FMEA with the DMAIC stage used to control quality from the initial process until a proposal for improvement is found. Obtained from the calculation results, the average sigma is 3.39 with an average DPMO of 29046.87 in production approval. The Pareto diagram of the most dominant defect percentages is final weft defects 27.8%, wavy 20.0%, loose weft 19.4%, non-woven 18.1%, double weft 14.7%. The highest RPN value was 280 for final feed defects and waves caused by workers' lack of accuracy regarding machine settings. Intensive training, process standardization, performance monitoring, use of checklists, increased communication, routine maintenance, use of technology..